PENDAPATAN USAHATANI TAMBAK BANDENG DI KECAMATAN UJUNGPANGKAH KABUPATEN GRESIK - Atini El Kifaf; Narni Farmayanti; Triana Gita Dewi (Universitas Teuku Umar, 2022)
Milkfish is one of the aquaculture commodities that has many advantages. The demand for milkfish always increases every year which is offset by the volume of production. In 2019, Kabupaten Gresik produced 54% of the total milkfish production in East Java Province. However, there was a decrease of milkfish production’s value so that it had implications for the income of fishermen. Therefore, this study aims to analyze the feasibilityof milkfish pond farming in Kabupaten Gresik. The analytical methods used are income analysis. The results of the study stated that milkfish pond farming in Kecamatan Ujungpangkah was economically feasible and profitable as indicated by the income value for the total cost of Rp21,595.613,00/ha and the R/C value of the total cost of 4.71.